Leading transformational change: Leveraging culture to create safe, healthy, and respectful workplaces - Junida, Isma; Marta, Rustono Farady; Panggabean, Hana; Salim, Mufid; Engliana, Engliana (Faculty of Communication Sciences Universitas Padjadjaran, 2025)
As a key player in the infrastructure sector, the organization's dedication to Occupational Safety and Health (OHS) is exemplified by the Corporate Life Saving Rule (CLSR) and various promotional activities, including the SHE Learn & Share Series SIG, commonly referred to as